A simplified method for design of geosynthetic tubes - Guo, Wei (2014)
A simplified method for the design of impermeable geosynthetic tubes inflated using liquid is proposed in this paper. Adopting a computer program for an existing theoretical model, relationships between pumping pressure and geometric parameters for geosynthetic tubes can be established. A set of simplified dimensionless design equations are then derived using the Chapman–Richard curve fitting method. The validity of this simplified method was verified using other established methods and laboratory model tests. The proposed simplified method can thus be used for routine or preliminary design.